Preparation and characterization of UV-cured epoxy/clay nanocomposite coatings on carbon steel. (22nd July 2016) - Varela Caselis, Jenaro L.; Sánchez, Marco Morales; Galicia Aguilar, José A.; Rosas, Efraín Rubio
ABSTRACT: Polymer-clay nanocomposites are compounds in which nanoclay particles are distributed in a polymer matrix. Epoxy-clay nanocomposites have become a very interesting topic among researchers in the past two decades because nanoclays have a positive effect on the mechanical, thermal and especially barrier anticorrosive performance of the polymers. In this study, epoxy-montmorillonite organoclay (OMMT) nanocomposite coatings were prepared and deposited on carbon steel substrates. The coatings were prepared through in situ polymerization and by UV-curing technique. The OMMT was added to epoxy resin at loadings between 0 wt.% and 5 wt.%, the particles of OMMT were dispersed using forced agitation-sonication and deposited on carbon steel coupons. The nanocomposite coatings obtained have been characterized by scanning electron microscopy (SEM), spectroscopy Fourier transform infrared (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and evaluated their corrosion protection effect on cold rolled carbon steel coupons by performing visual analysis. The X-ray analysis showed that exfoliation occurred for the OMMT in the polymer matrix, the SEM analysis showed that OMMT was homogenous dispersed in the polymer matrix and the coatings were uniform. The FTIR analysis showed the characteristic bands of epoxy resin and OMMT in the composite. The results showed that 1 wt.% OMMT coating exhibit better anticorrosive properties than pure epoxy.